2016
DOI: 10.3329/bjms.v15i4.24962
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Associated Pneumonia a challenge in intensive care unit acquired infection

Abstract: Background: Ventilator-Associated Pneumonia (VAP) is one of the frequent intensive-care-unit (ICU)-acquired infection. The aetiology of VAP varies with patients' profiles and ICU settings. Due to the increasing incidence of multidrug-resistant organisms in ICUs, early and correct diagnosis of VAP is an urgent challenge for an optimal antibiotic treatment. The aim of the study was to assess the incidence of VAP in different patients by various organisms to create a database of the causative agents of VAP, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The findings of the study carried out by Turković and collaborators highlighted that Acinetobacter baumanii were 8.0% resistant to ampicillin/salbactem and 63% resistant to meropenem [15]. A study done by Sarkar et al showed that Acinetobacter baumanii were 30% sensitive to tigecycline [18]. Study further disclosed that E. coli were 60.0% resistant to ampicillin/salbactem, piperacillin, cefuroxime, cefuroxime axetil, cefixime, ceftriaxone, cefepime, aztreonam, meropenem, levofloxacin, moxifloxacin and chloramphenicol, 40% resistant to tetracycline, trimethoprim while sensitive to minocycline and colistin.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study carried out by Turković and collaborators highlighted that Acinetobacter baumanii were 8.0% resistant to ampicillin/salbactem and 63% resistant to meropenem [15]. A study done by Sarkar et al showed that Acinetobacter baumanii were 30% sensitive to tigecycline [18]. Study further disclosed that E. coli were 60.0% resistant to ampicillin/salbactem, piperacillin, cefuroxime, cefuroxime axetil, cefixime, ceftriaxone, cefepime, aztreonam, meropenem, levofloxacin, moxifloxacin and chloramphenicol, 40% resistant to tetracycline, trimethoprim while sensitive to minocycline and colistin.…”
Section: Discussionmentioning
confidence: 99%
“…Piperacillintazobactum was also ineffective against most of the organisms reported by Sarkar et al which is similar to this study. 24 The emergence of MDR bacteria has forced us to think about polymyxins, especially colistin. 25 But the frequent use of this reserve antibiotic, colistin resistance strains have developed.…”
Section: Discussionmentioning
confidence: 99%